Pengaruh Therapi Kognitif Behavior Terhadap Perilaku Merokok - Wittin Khairani (Universitas Batanghari Jambi, 2019)
Indonesia is the country with the largest number of young smokers in Asia. At the age of adolescents (aged 12-18 years) or at the age of the Junior High School level, it is very potential to become a new smoker. This phenomenon of new smokers often occurs among adolescent children due to the association and environmental influences. Therefore there must be an early effort to provide an understanding of the dangers of smoking and the impact on health. This study aims to determine the effect of cognitive therapy behavior on smoking behavior. The research method used a quasi-experimental design with one group design with pretest and posttest. Sampling was 30 people by purposive sampling. Data analysis using paired t-test (p-value 0.05) to see the effect of cognitive behavioral therapy on knowledge, attitudes and behavioral tendencies. Furthermore, using the independent t-test statistical test to see the difference in cognitive behavioral therapy to knowledge, the tendency of behavior (intention) to smoke. The results of the study are the influence of cognitive behavior therapy on knowledge, attitudes, and tendencies of smoking behavior in junior high school students. It is expected that the results of this study can contribute to the mind in choosing an effective therapeutic method in carrying out the duties and responsibilities of health promotion practitioners to maintain, prevent, treat, recover and improve the health status of the community.